Inequities in glaucoma research: an analysis of Cochrane systematic reviews and randomized trials - Bondok, Mostafa; Dewidar, Omar; Al-Ani, Abdullah; Selvakumar, Rishika; Ing, Edsel; Ramke, Jacqueline; El-Hadad, Christian; Damji, Karim F.; Li, Tianjing; Welch, Vivian (Journal of clinical epidemiology, 2025)
To understand the level of equity considerations within Cochrane systematic reviews (CSR) on glaucoma and their primary studies. A review of equity considerations in systematic reviews on glaucoma published in The Cochrane Library from inception (2003) to January 31, 2024 and a sample of recently published primary studies included in those reviews (n = 122). Extraction was performed by two independent reviewers using a prepiloted extraction form based on a validated, contemporary, structured equity framework. If consensus could not be reached, a third reviewer was involved. A total of 40 CSRs on glaucoma were identified, all of which exclusively included randomized control trials (RCTs) or quasi-RCTs. Twenty-nine (72.5%) reviews acknowledged populations experiencing inequities in glaucoma care; none were able to perform subgroup analysis due to data unavailability in primary studies. Six (15.0%) reviews considered equity-relevant factors when discussing applicability or limitations of study findings to specific populations. Seventy-four (46.8%) review authors were women, while 84 (53.2%) were men. Most review authors were primarily affiliated with institutions in the European Region (85, 53.8%) or the Americas (55, 34.8%), while none were primarily affiliated with institutions in Africa or low-income countries. Most RCTs were conducted in the Americas (32.8%), European Region (27.9%), or in high-income countries (72.1%). While most RCTs reported gender or sex of participants (107, 87.7%), only half reported race or ethnicity (61, 50.0%). No RCTs reported place of residence, occupation, socioeconomic status (SES), or social capital of participants. Approximately half (51.7%) of the participants in these RCTs were female. Equity considerations can be better addressed in research on glaucoma. Reporting of patient sociodemographic in RCTs, particularly race and ethnicity, as well as global representation were insufficient. This may limit the generalizability and applicability of intervention efficacy to populations experiencing inequities and people from low-income countries. •Study participants in glaucoma trials are primarily from high-income countries.•Gender parity exists among authors, but geographic diversity is still lacking.•Racial and ethnic diversity gaps remain in glaucoma research.•There is an urgent need to address the equity gaps in glaucoma research.•Limited sociodemographic diversity in trials may affect study generalizability.